2015
DOI: 10.1016/j.colsurfb.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

45S5Bioglass®-based scaffolds coated with selenium nanoparticles or with poly(lactide-co-glycolide)/selenium particles: Processing, evaluation and antibacterial activity

Abstract: In the bone tissue engineering field, there is a growing interest in the application of bioactive glass scaffolds (45S5Bioglass(®)) due to their bone bonding ability, osteoconductivity and osteoinductivity. However, such scaffolds still lack some of the required functionalities to enable the successful formation of new bone, e.g. effective antibacterial properties. A large number of studies suggest that selenium (Se) has significant role in antioxidant protection, enhanced immune surveillance and modulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…In addition to silver nanoparticles that have been widely studied for anti-bacterial/microbial applications, graphene oxide [208] and selenium nanoparticles have been demonstrated to be excellent candidates for this purpose [211, 212]. One recent study indicated a significant decrease in long term proliferation of osteoblast-like sarcoma cells, while the proliferation of osteoblasts were two times higher, indicating the dual purpose of these nanoparticles.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…In addition to silver nanoparticles that have been widely studied for anti-bacterial/microbial applications, graphene oxide [208] and selenium nanoparticles have been demonstrated to be excellent candidates for this purpose [211, 212]. One recent study indicated a significant decrease in long term proliferation of osteoblast-like sarcoma cells, while the proliferation of osteoblasts were two times higher, indicating the dual purpose of these nanoparticles.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Stevanovic et al prepared uniform, amorphous, stable selenium nanoparticles immobilized inside spherical PLGA particles (PLGA/Se). Bioactive glass based constructs coated with PLGA/Se nanoparticles using foam replica method proved to be a promising candidate in bone tissue repair and rejuvenation by promoting bone regeneration and eliminating possible infections and inflammations[58]. In another study, nanosized mesoporous bioactive glass (NMBG) nanoparticles were prepared and coated onto PLGA-calcium silicate scaffolds for better mechanical strength, drug delivery and bioactivity in BTE.…”
mentioning
confidence: 99%
“…Several studies have shown that BG is angiogenic, 16 osteoconductive, 17,18 and osteoinductive. 19 BG also supports osteoblasts, which are vital for adhesion, growth, differentiation, and new bone formation in bone tissue engineering.…”
Section: 15mentioning
confidence: 99%